2011
DOI: 10.1111/j.1369-7625.2011.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Pictures speak louder than numbers: on communicating medical risks to immigrants with limited non‐native language proficiency

Abstract: Background and objectives Medical risk communication has been infrequently studied in immigrants with limited non-native language proficiency, even though they may be at greatest risk of illness. In a study, we examined to what extent Polish immigrants to the UK have difficulties in understanding treatment risk reduction expressed as ratios either in their native language or in a non-native language (English). We further investigated whether this population can be aided by using visual displays to enhance comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 61 publications
1
41
0
3
Order By: Relevance
“…Individuals with low numeracy skills are better able to understand, and recall numerical information when presented with visual aids [22][23][24][25]. This is especially the case in individuals with high graphical literacy [25] -the ability to understand graphical representations used to present quantitative health information.…”
Section: Introductionmentioning
confidence: 93%
“…Individuals with low numeracy skills are better able to understand, and recall numerical information when presented with visual aids [22][23][24][25]. This is especially the case in individuals with high graphical literacy [25] -the ability to understand graphical representations used to present quantitative health information.…”
Section: Introductionmentioning
confidence: 93%
“…Both novices and trained experts benefit from the implementation of simple visual representations of risk information, whether they are evaluating medical treatments or new counterterrorism techniques (Garcia-Retamero & Dhami, 2011; (Fox & Sitkin, 2015).…”
Section: Optimizing Choice Architecturementioning
confidence: 99%
“…They can also promote consideration of beneficial treatments that have side effects (Waters, Weinstein, Colditz, & Emmons, 2007), limit errors induced by anecdotal narratives (Fagerlin, Wang, & Ubel, 2005), and framed messages (Garcia-Retamero & Galesic, 2010a), and reduce biases (Garcia-Retamero & Dhami, 2011;Garcia-Retamero & Galesic, 2009a;Garcia-Retamero et al, 2010). Research by Galesic, Garcia-Retamero, and Gigerenzer (2009;see also Garcia-Retamero & Galesic, 2010b) showed that visual aids are useful when the risk information is presented both in complex numerical formats such as relative risk reduction (e.g., aspirin can reduce the risk of having a stroke or heart attack by 13% in people with symptoms of arterial disease) and in numerical formats that are relatively easy to understand (absolute risk reduction; e.g., aspirin can reduce the risk of having a stroke or heart attack from 8% to 7% in people with symptoms of arterial disease).…”
mentioning
confidence: 99%